Clinical features of early multiple sclerosis - Čelpačenko, I.; Stankevičiūtė , R.; Malciūtė, M.; Balnytė, R. (Neurologijos seminarai, 2021)
Background. In recent years, the incidence rate of multiple sclerosis (MS) has been increasing worldwide. Its heterogeneous presentation in combination with various conditions mimicking MS presents great diagnostic difficulties. Delayed treatment increases the risk of disability, therefore, establishing a clear phenotype of early MS can help in a more efficient diagnostic process. This study aimed to establish clinical features of early multiple sclerosis. Materials and methods. A retrospective analysis of data was performed in patients hospitalized with the following ICD-10 (International Classification of Diseases Version 10) diagnoses: G37.8 (other specified demyelinating diseases of central nervous system) and G37.9 (demyelinating disease of central nervous system, unspecified). Patients hospitalized from January 1, 2015 to January 1, 2020 were included. The data was obtained from medical records and included sex, age, neurological signs and symptoms, risk factors associated with MS, and final diagnosis. Chi-squared test was used to compare categorical variables. The relationship between two quantitative variables was performed using Spearman correlation coefficient. Mann-Whitney U test and independent-samples t-test were used for comparison between groups. The results were interpreted as statistically significant when p-value < 0.05. Results. A total of 138 patients were included in the study: 92 (64.5%) women and 46 (35.5%) men. The patients were divided into the following age groups: 28 (20.3%) patients aged 18-30 years (mean 24.89±3.725), 58 (42.0%) aged 31-50 years (mean 40.43±6.093), and 52 (37.7%) 50 years and older (mean 57.83±5.498). 49 (35.5%) patients converted to MS and 89 (64.5%) patients were diagnosed with other diseases than MS. Patients converted to MS (n=20) were more likely to have a diminished sense of vibration and proprioception compared with non-converted patients (n=16), (χ2=9.033, p=0.003). No other differences were found between converted and non-converted patients. Converted females (n=10) were more likely to have positive Rossolimo’s reflex than converted males (n=2), (χ2=4.451, p=0.035). Converted patients older than 50 years presented with more symptoms (U=10.519, p=0.005) compared with younger patients and were more likely to have positive Babinski’s reflex (n=13), (χ2=6.993, p=0.03), decreased muscle strength (n=14), (χ2=13.481, p=0.001), ataxia (n=13), (χ2=8.135, p=0.017), and diminished sense of vibration and proprioception (n=12), (χ2=7.918, p=0.019). Conclusion. Diminished sense of vibration and proprioception was more common in MS group. Positive Rossolimo’s reflex was more prevalent among converted females, whereas MS patients older than 50 years had more neurological signs and symptoms than younger patients. Positive Babinski’s reflex, decreased muscle strength, ataxia, and diminished sense of vibration and proprioception were more frequent in patients older than 50 years compared with younger patients.